MANAGEMENT OF AMERICAN BOLLWORM (HELICOVERPA ARMIGERA) USING NATIVE ISOLATED SPODOPTERA LITURA ASSOCIATED NUCLEOPOLYHEDRO VIRUSES (SlitNPV) - J. N. Ahmad; S. J. N. Ahmad; M. Jafir; M. Manzoor; M. A. Malik; M. Tariq (Journal of Animal and Plant Sciences, 2022)
Helicoverpa armigera (Lepidoptera, Noctuidae) is polyphagous insect pests of many economically important crops. In present research, native Nucleopolyhedroses virus (SlitNPV) were isolated from infected Spodoptera litura present in cotton field and observed under microscope through Geimsa Stain. Viral suspensions were prepared for bioassays. To observe the effect of Nucleopolyhedroses virus (NPV) and Spinosad, various doses of sub-lethal (< LC50) and lethal (>LC50) were applied alone and in combination with Spinosad (0.01 ppm). The biological activities of native NPV isolate and its interaction were studied against larvae of H. armigera (2nd and 4th instars). The biological attributes were severely affected and highest mortality of H. armigerawas observed at early instars as compared to last larval instars. The mortality and means of H. armigera was done using Abbott’s formula and Tukey-Kramer (HSD) test. The additive and synergistic interaction was found among different instars against various doses of NPVs and spinosad. A synergistic interaction of lethal dose of NPV (lethal (>LC50) was observed with spinosad against 2nd as well as 4th instar larvae of H. armigera. The current study suggests that environment friendly biological insecticides should be developed that can effectively be used to manage different insect pests of major crops by reducing and the use of synthetic chemicals and encourages developing. The results from this study indicated that S. litNPV was effective against H. armigera and can easily be used to manage these pests successfully confirming an alternative strategy than commercial based insecticide.
Keywords: Nucleopolyhydroviruses; Insect pest management; Microbial insecticides; PCR